If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -7 = -5x Reorder the terms: -7 + 3y = -5x Solving -7 + 3y = -5x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 3y = 7 + -5x Combine like terms: -7 + 7 = 0 0 + 3y = 7 + -5x 3y = 7 + -5x Divide each side by '3'. y = 2.333333333 + -1.666666667x Simplifying y = 2.333333333 + -1.666666667x
| b(b-2)=b | | 2x-6y= | | n^2=10n+3000 | | -56+[-14]=4x+5 | | .12x+.16y=6 | | l(x)-l(x+5)=0 | | 0.28x-1.2= | | 3a^3+a^2=2a | | 2.4+0.4x= | | 35+w^2=12w | | lo(x)-lo(x+5)=0 | | 600=10c+5s | | 3n=12+n+26 | | -4x+30=3x-10 | | -5x-2=3 | | 0.28x-10-1.2= | | -4x+30=13x-10 | | x^2+kx+30=x^2+3x-10 | | 2.4+0.4x-10= | | 0=a^2-6a-100 | | -12+24y=-60 | | logx-log(x+5)=0 | | 2.4+0.4x-30= | | 4x-.8=2.2 | | 13x+1=11t+9 | | -16=8h-4h | | 29=x-44 | | x^2-4x+7=7 | | (-7)(-14)0.7= | | 4x+.8=2.2 | | Y=4(2x+7) | | -3f-7-8f=16 |